2013
DOI: 10.1007/s10096-013-1848-2
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium invasive infections in children: a retrospective study in two French tertiary care centres

Abstract: The purpose of this investigation was to describe the clinical and biological characteristics and evolution of invasive Fusobacterium infections in children admitted to two French paediatric tertiary care centres. Children who were admitted from 1998 to 2009 to two tertiary care centres for invasive Fusobacterium infection were included in a retrospective study. Thirty-one children with a median age of 5.7 years (interquartile range, IQR [2.3; 9.3]) were included. Nine children had an underlying condition, mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Other central nervous system complications were frequent in our series, including decreased level of consciousness at admission (22.7 %), meningitis (18 %) and CSVT (22.7 %). Interestingly, none of the children experienced seizures, compared with 3-30 % in other pediatric series [8,11]. Fusobacterium meningitis is rarely reported in the literature, mostly appearing in scattered case reports [18,27,28].…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Other central nervous system complications were frequent in our series, including decreased level of consciousness at admission (22.7 %), meningitis (18 %) and CSVT (22.7 %). Interestingly, none of the children experienced seizures, compared with 3-30 % in other pediatric series [8,11]. Fusobacterium meningitis is rarely reported in the literature, mostly appearing in scattered case reports [18,27,28].…”
Section: Discussionmentioning
confidence: 81%
“…The true contribution of Fusobacterium can be questioned by the simultaneous presence of other pathogens in some cases (polymicrobial infections were observed in 27 % of the patients). In other series, however, polymicrobial infections were observed in up to half of cases with Fusobacterium infections [5,8]. Previous studies have demonstrated that the presence of Fusobacteria spp.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations